Biochemical alterations during medication withdrawal in Parkinson's disease with and without neuroleptic malignant-like syndrome. Issue 1 (1st July 2001) - Ueda, M; Hamamoto, M; Nagayama, H; Okubo, S; Amemiya, S; Katayama, Y
Abstract : The object was to assess alterations in CSF concentrations of monoamine metabolites during withdrawal of medication in patients with Parkinson's disease in relation to the presence or absence of episodes resembling neuroleptic malignant syndrome (NMS). This syndrome is a fatal condition developing after neuroleptic therapy, and a neuroleptic malignant-like syndrome (NMLS) may also occur after withdrawal of antiparkinsonian drugs in patients with Parkinson's disease. Previous biochemical assays showed that the CSF concentration of the dopamine metabolite homovanillic acid (HVA) is an independent prognostic factor for development of NMLS in patients with Parkinson's disease. In the present study, CSF concentrations of HVA, the noradrenaline (norepinephrine) metabolite 3-methoxy-4-hydroxyphenylethylene glycol, and the serotonin metabolite 5-hydroxyindole acetic acid were assayed using high performance liquid chromatography with electrochemical detection. The study population consisted of nine patients with Parkinson's disease with NMLS and 12 without NMLS, in whom metabolites were assayed during both withdrawal and remedicated periods. Concentrations of HVA in the CSF were significantly lower during the withdrawal period than the medicated period regardless of whether patients developed NMLS, and HVA concentrations were comparably increased after remedication in both groups. However, HVA concentrations were significantly lower in patients with NMLS than in those without NMLS during both withdrawal and medicated periods. Other metabolites showed no significant differences. The present data provide further biochemical evidence for extremely suppressed central dopaminergic activity during NMLS, which may indicate a narrow safety margin for medication withdrawal in patients with Parkinson's disease.